(untitled) (Journal of Plant Disease Sciences, 2025)
Various Phytophthora species have long been associated with different citrus diseases, including gummosis, root rot, fruit brown rot, and citrus decline worldwide, including in India. Among these, Phytophthora parasitica has gained considerable attention due to its significant role in causing citrus gummosis, a major factor contributing to yield losses. Studies have shown that P. parasitica can lead to approximately 10–30% yield reduction due to gummosis. Considering this impact, the present study aims to synthesize copper nanoparticles (CuNPs) and evaluate their antifungal efficacy against P. parasitica. Due to their large specific surface area and low cost, copper nanoparticles have garnered substantial interest. In this study, CuNPs were successfully synthesized using a novel, simple method based on the chemical reduction of aqueous copper salt at low temperatures (80 °C), with ascorbic acid acting as a reducing agent. The maximum absorbance at 340 nm in the UV-Vis spectroscopic analysis confirmed the presence of CuNPs in the reaction mixture. Efficacy experiments revealed that CuNPs at 50 ppm and 100 ppm concentrations significantly inhibited the mycelial growth of P. parasitica by 59.25% and 100%, respectively. Overall, the present study highlights the potential of synthesized CuNPs as a nano-fungicide at low concentrations, offering an eco-friendly alternative to synthetic fungicides and helping to reduce harmful environmental impacts.